Ectopic expression of sugarcane SHINE changes cell wall and improves biomass in rice - Martins, Alexandre Palma Boer; Brito, Michael dos Santos; Mayer, Juliana Lischka S.; Llerena, Juan Pablo Portilla; Oliveira, Jasmim Felipe; Takahashi, Natália Gonçalves [UNESP]; Carlin, Samira Domingues; Borges, Denisele Neuza Aline Flores; Andrade, Larissa Mara; Peixoto-Júnior, Rafael Fávero; Goldman, Maria Helena de Souza; Mazzafera, Paulo; et al. (Elsevier, 2018)
One of the major challenges involved in biofuel production from plant biomass is increasing the saccharification efficiency impaired by cell wall recalcitrance. The sugarcane transcription factor ShSHN1 was overexpressed in rice to evaluate its impacts on cell wall composition and potential for the development of refined lignocellulosic feedstocks for biofuel manufacturing. Plant phenotyping included biomass and cell wall component determination. Additionally, gene expression of biosynthetic cell wall polymers and wax/cutin-related genes were evaluated. ShSHN1 ectopic overexpression promoted an increase in biomass (91–340%), pectin (26–209%), cellulose content (10–22%) and saccharification efficiency (5–53%) in rice transgenic plants, as well as a reduction in the lignin content (17–35%) and an altered lignin composition. Such an increase in pectin is a new finding and opens up new research pathways for cell wall manipulation of energy crops. Furthermore, ShSHN1 overexpression led to changes in the expression patterns of all genes analyzed, suggesting a possible relation between ShSHN1 and the regulatory mechanisms involved in secondary plant cell wall formation. Saccharification improvement and biomass increase made the perfect combination for second generation ethanol production. This synergistic gain is discussed based on structural polysaccharides and lignin modification. Phenotypes and gene expression analysis provide insights into possible SHINE mechanisms of action and biological role in cell wall component biosynthesis. These results demonstrate the great potential of ShSHN1 to improve grass feedstocks as a source of energy.
Keywords: 2G ethanol; Biomass; Cell wall; Saccharification; Sugarcane; Transcription factor